(untitled) (Revista Innova Educación, 2025)
The decision to pursue a university degree is shaped by multiple personal and contextual dimensions that affect students’ academic and professional trajectories. In the case of Accounting Sciences, available studies address these determinants only partially and across heterogeneous contexts, which hinders an integrated understanding of the phenomenon. In response, this study aimed to identify and classify the factors that influence the choice of an Accounting Sciences degree. A systematic literature review was conducted in accordance with PRISMA guidelines, considering publications from 2013 to 2025 indexed in the Scopus and SciELO databases. Based on previously defined inclusion and exclusion criteria, 21 studies were selected for analysis. The evidence shows that career choice is recurrently linked to personal factors (interest, vocation, and self-efficacy), perceptual factors (image and social valuation of the profession), and labor-market factors (expectations regarding employability and stability). Overall, these findings indicate that choosing Accounting Sciences results from a complex interaction of motivations and perceptions, suggesting the need to strengthen vocational guidance strategies through a comprehensive and contextualized approach.